Representasi Analisis Kebebasan dan Penjara Sosial dalam Tayangan Film Barbie - Salma Puteri Andanie; Misyi Gusthini (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This study analyzes how the film Barbie depicts freedom and social constraints, focusing on how these themes emerge through the characters and story. The aim of this analysis is to provide an understanding of how Barbie reflects modern issues related to identity, empowerment, and the challenges of achieving true freedom in a society filled with rules. As Greta Gerwig (2023) stated, "I thought I was living in a perfect world, with no problems, but I started to see there were many things blocking me from truly being free." The film depicts Barbie’s journey of self-discovery as she challenges traditional gender roles and confronts societal expectations. According to Miller (2023), although the film conveys a message of liberation, it also shows that the struggle against strong social norms is ongoing. The research method used in this study is qualitative narrative analysis, where the author examines the narrative, characters, and symbolism in Barbie to explore how the themes of freedom and social confinement are represented. The findings of this study indicate that Barbie portrays the complexity of freedom in a society controlled by rigid gender norms, while also highlighting the importance of solidarity among women in overcoming social barriers. The film sends a message about how the courage to defy social norms can bring about change and individual liberation.